Masques : revue des homosexualités (Paris: Masques)
"Fonds Suzan Daniel (FSD)Periodiciteit: driemaandelijks. Doorlopende nummering.Redactie: c/o Librairie Anima, 3 rue Ravignan, 75018 Paris ; vanaf (1981) 11: BP 126, 75863 Paris. Cedex 18"